2018
DOI: 10.1177/1758834017745819
|View full text |Cite
|
Sign up to set email alerts
|

Abiraterone acetate and prednisone in the pre- and post-docetaxel setting for metastatic castration-resistant prostate cancer: a mono-institutional experience focused on cardiovascular events and their impact on clinical outcomes

Abstract: Background:The aim of this work was to to evaluate the incidence and risk factors of adverse events (AEs), focusing on cardiovascular events (CVEs) and hypokalemia, in patients treated with abiraterone acetate (AA) and prednisone (PDN) outside clinical trials, and their association with survival outcomes.Methods:This was a retrospective cohort study of 105 patients treated from 2011 to 2016. Incidence of AEs was descriptively summarized in the whole cohort and by subgroup (pre- versus post-docetaxel). Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
(71 reference statements)
3
11
0
Order By: Relevance
“…In agreement with previous real-world studies, 18 , 20 , 22 , 24 26 , 28 , 37 , including Italian ones, 21 , 27 our findings confirm, in a real-life setting, the efficacy and safety of abiraterone demonstrated in the registration trial (COU-AA-302), despite the poorer clinical features of the enrolled patients, including the advanced age (60% of our patients were ⩾75 years old) and the high prevalence of comorbidity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous real-world studies, 18 , 20 , 22 , 24 26 , 28 , 37 , including Italian ones, 21 , 27 our findings confirm, in a real-life setting, the efficacy and safety of abiraterone demonstrated in the registration trial (COU-AA-302), despite the poorer clinical features of the enrolled patients, including the advanced age (60% of our patients were ⩾75 years old) and the high prevalence of comorbidity.…”
Section: Discussionsupporting
confidence: 92%
“…Abiraterone was well tolerated in our cohort of elderly patients with pre-existing cardiac disorders, in line with previous real-life observations. 21 , 44 46 In the largest study published so far by Boegemann et al ., 22 2% of patients discontinued due to toxicity, 8% of patients had an ADR and <1% had a serious ADR. In our study similar numbers were reported: discontinuation of therapy because of toxicity occurred in 5% of patients, and 13% of patients had an ADR; only 1.7% reported a serious ADR.…”
Section: Discussionmentioning
confidence: 99%
“…A few years ago, Cavo et al evaluated the correlation between risk factors of adverse events and survival outcomes in mCRPC patients treated with abiraterone acetate and prednisone, observing that at multivariable analysis BMI >25 kg/m 2 resulted significantly associated both with worse progression-free survival and worse overall survival (OS) ( p = 0.03 and p = 0.042, respectively) [94]. Furthermore, a research group headed by Antoun retrospectively analyzed whether body composition parameters affected prognosis of mCRPC patients treated with androgen receptor inhibitors abiraterone acetate and enzalutamide into two prospective clinical trials [95,96], showing that no relationship between BMI and OS was detected [97].…”
Section: Correlation Between Obesity and Response To Therapy In Prmentioning
confidence: 99%
“…However, inhibition of CYP17A1 by abiraterone can lead to glucocorticoid insufficiency and mineralocorticoid excess. Hypertension, hypokalemia and peripheral edema occur with sufficient frequency that abiraterone is co-administered with prednisone [34] , [35] , [36] .…”
Section: Cyp17a1 Activity Inhibitors and Mechanisms Of Pca Resistancmentioning
confidence: 99%